Impacts of abiotic stresses on the physiology and metabolism of cool‐season grasses: A review. (7th October 2018) - Loka, Dimitra; Harper, John; Humphreys, Mike; Gasior, Dagmara; Wootton-Beard, Peter; Gwynn‐Jones, Dylan; Scullion, John; Doonan, John; Kingston‐Smith, Alison; Dodd, Rosalind; Wang, Jinyang; Chadwick, David; et al.
Abstract: Grasslands cover more than 70% of the world's agricultural land playing a pivotal role in global food security, economy, and ecology due to their flexibility and functionality. Climate change, characterized by changes in temperature and precipitation patterns, and by increased levels of greenhouse gases in the atmosphere, is anticipated to increase both the frequency and severity of extreme weather events, such as drought, heat waves, and flooding. Potentially, climate change could severely compromise future forage crop production and should be considered a direct threat to food security. This review aimed to summarize our current understanding of the physiological and metabolic responses of temperate grasses to those abiotic stresses associated with climate change. Primarily, substantial decreases in photosynthetic rates of cool‐season grasses occur as a result of high temperatures, water‐deficit or water‐excess, and elevated ozone, but not CO2 concentrations. Those decreases are usually attributed to stomatal and non‐stomatal limitations. Additionally, while membrane instability and reactive oxygen species production was a common feature of the abiotic stress response, total antioxidant capacity showed a stress‐specific response. Furthermore, climate change‐related stresses altered carbohydrate partitioning, with implications for biomass production. While water‐deficit stress, increased CO2, and ozone concentrations resulted in higher carbohydrate content, the opposite occurred under conditions of heat stress and flooding. The extent of damage is greatly dependent on location, as well as the type and intensity of stress. Fortunately, temperate forage grass species are highly heterogeneous. Consequently, through intra‐ and in particular inter‐specific plant hybridization (e.g., Festuca x Lolium hybrids) new opportunities are available to harness, within single genotypes, gene combinations capable of combating climate change. Abstract : Grasslands cover more than 70% of the world 's agricultural land playing a pivotal role in global food security, economy, and ecology due to their flexibility and functionality. Climate change, characterized by changes in temperature and precipitation patterns, and by increased levels of greenhouse gases in the atmosphere, is anticipated to increase both the frequency and severity of extreme weather events, such as drought, heat waves, and flooding. This review aimed to summarize the current knowledge of the effects of encountering and responding to abiotic stresses particularly associated with climate change on the physiology and metabolism of cool‐season forage grass and turf grass species.